2015
DOI: 10.1177/0308022614562582
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Australian Therapy Outcome Measures for Occupational Therapy (AusTOMs-OT) in an early supported discharge programme for stroke patients in Singapore

Abstract: Introduction: This short report describes the use of the Australian Therapy Outcome Measures for Occupational Therapy (AusTOMs-OT) in an early supported discharge programme for stroke patients in Singapore. Method: The Australian Therapy Outcome Measures for Occupational Therapy was assessed at the start and end of the early supported discharge programme and differences were statistically analysed. Findings: All Australian Therapy Outcome Measures for Occupational Therapy scales demonstrated statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…However, as participation and distress/wellbeing are global constructs, these are scored once, across all scales at admission and again at discharge. Studies have demonstrated the validity (Abu-Awad et al, 2014; Chen and Eng, 2015; Unsworth, 2005; Unsworth et al, 2004) and reliability (Fristedt et al, 2013; Morris et al, 2005; Scott et al, 2006; Unsworth et al, 2018) of the AusTOMs-OT. In addition, Unsworth et al (2015) investigated the minimal clinically important difference (MCID), indicating a clinically significant change, for each AusTOMs-OT scale as being a one-point shift.…”
Section: Methodsmentioning
confidence: 99%
“…However, as participation and distress/wellbeing are global constructs, these are scored once, across all scales at admission and again at discharge. Studies have demonstrated the validity (Abu-Awad et al, 2014; Chen and Eng, 2015; Unsworth, 2005; Unsworth et al, 2004) and reliability (Fristedt et al, 2013; Morris et al, 2005; Scott et al, 2006; Unsworth et al, 2018) of the AusTOMs-OT. In addition, Unsworth et al (2015) investigated the minimal clinically important difference (MCID), indicating a clinically significant change, for each AusTOMs-OT scale as being a one-point shift.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the AusTOMs' validity was established through comparisons between AusTOMs scores and EuroQol-5D scores, resulting in Spearman Rho correlations of 0.612-0.748 (Unsworth et al, 2004). This validity has been supported in ongoing studies using AusTOMs (Abu-Awad et al, 2014;Chen & Eng, 2015;Unsworth, 2005). Multiple reliability studies have been conducted (Fristedt, Elgmark Andersson, & Unsworth, 2013;Morris et al, 2005;Scott, Unsworth, Fricke, & Taylor, 2006), with the most recent study revealing inter-rater reliability intraclass correlation coefficients (ICCs) ranging from 0.531 to 0.922 suggesting moderate to very high reliability, and intra-rater reliability ICCs between 0.675 to 1.000 suggesting moderate to very high reliability (Unsworth, Timmer, & Wales, 2018).…”
Section: Instrumentmentioning
confidence: 95%
“…The most commonly documented AusTOMs-OT scales in the literature are self care, upper limb use, functional walking and mobility, domestic life-home, and community life/recreation/leisure/play (Abu-Awad et al, 2014;Chen & Eng, 2015;Unsworth, 2008;Unsworth et al, 2009;Unsworth et al, 2005). Considering this and the available data, this study also focused the data analysis on these five more common AusTOMs-OT scales.…”
Section: Instrumentmentioning
confidence: 99%